Decoding the mise-en-scène of contemporary secular spirituality: a research monograph. Parts II and III contrasting the mise-en-scène of medieval Christian spirituality with that of contemporary consumerist lifestyle: sociological and educational implications - Rossiter, Graham (Journal of Religious Education, 2014)
Following on from the publication in the last issue of this journal, these two parts of the monograph use the construct mise-en-scène for contrasting traditional medieval Christian spirituality with the contemporary secular spirituality that is implied in a consumerist lifestyle, particularly in the way that both are expressed through visual imagery. While in two very different cultures at distinct periods of history, both have been dominated by a universal visual iconography that mediated powerful cultural sources of meaning and values; these were like the pillars that structured a unified social reality for the people of the time, shaping their views of meaning and purpose to life. The dominant cultural imagery in both situations conditioned the perceived underlying narrative or mise-en-scène for life. In addition to providing educators with a way of interpreting contemporary spirituality, the approach illustrates a religious education pedagogy for exploring spiritual and moral dimensions to contemporary living in contrast with the way life was interpreted in the past from an almost exclusively religious perspective.